Comparing the development of Local Industrial Strategies across the Northern Powerhouse: Key emerging issues. (June 2020) - Shutt, John; Liddle, Joyce
Will the UK Industrial Strategy deliver anything substantial to the North of England? This article examines the faltering steps taken to develop Local Industrial Strategies by Local Enterprise Partnerships and Mayoral Combined Authorities and argues Place Leadership and Industrial Strategy will both need to be substantially re-galvanised after COVID 19. It is also still not clear if a significant step change can be made by the Johnson Conservative government of 2019, which will have a major impact on Northern economies. Agencies' capacity to intervene in the Northern economy and deliver is a major issue, alongside stronger leadership. Analytically the paper uses theory on Multi-Sectoral Collaboration and Place Leadership to show how uniqueness of place, past and current interpersonal connections and networks can facilitate or frustrate economic development. Place leaders must create institutional arrangements, seek agreement over visions, objectives and strategies, otherwise the lack of shared information, resources, activities and capabilities lead to 'contestation' over space and action. We analyse the levels of cohesion or contestation in four different localities as each develops a Local Industrial Strategy.